Relación entre autoestima y celos en adultos jóvenes estudiantes de la Universidad de la Costa (2019)
This study aims to evaluate the relationship between self-esteem and jealousy, in a population sample of young adults in the city of Barranquilla. This research was develop under a quantity approach with a correlational design. The sample was composed of 295 students from Universidad de la Costa of ages between 18 and 24 years, of these, 140 were men and 151 were women. As a data collection, was used the Rosenberg Self-esteem, the Spanish adaptation of Romantic Jealousy Scale by Montes and Berges (1989) and a socio-demographic survey. The results reflected that there were no meaning statistical differences in the self-esteem level between man and women, while it is found in jealousy levels. The women showed a higher level of jealousy in comparison with men. Besides, it was found that higher self-esteem related to lowest levels of jealousy towards the couple.